The role of ruminant urine and faeces in the recycling of nutrients by forages - Kao, Pei-Tzu; McGrath, Steve P.; Buss, Heather L.; Darch, Tegan; Warren, Helen E.; McAuliffe, Graham A.; Cardenas, Laura; Blackwell, Martin; Lee, Michael R. F. (Scientific reports, 2024)
This study addresses the effect of using animal excreta on the nutritional content of forages, focusing on macro- and micro-element concentrations (nitrogen; N, phosphorus; P, sulphur; S, copper; Cu, zinc; Zn, manganese; Mn, selenium; Se) from animal feed to excreta, soil, and plants. Data were collected from pot and field trials using separate applications of sheep or cattle urine and faeces. Key findings indicate that soil organic carbon (SOC) and the type of excreta significantly influences nutrient uptake by forages, with varied responses among the seven elements defined above. Although urine contributes fewer micronutrients compared to faeces (as applied at a natural volume/mass basis, respectively), it notably improves forage yield and micronutrient accumulation, thus potentially delivering positive consequences at the farm level regarding economic performance and soil fertility when swards upon clayey soil types receive said urine in temperate agro-climatic regions (i.e., South West England in the current context). In contrast, faeces application in isolation hinders Se and Mn uptake, once again potentially delivering unintended consequences such as micronutrient deficiencies in areas of high faeces deposition. As it is unlikely that (b)ovine grazing fields will receive either urine or faeces in isolation, we also explored combined applications of both excreta types which demonstrates synergistic effects on N, Cu, and Zn uptake, with either synergistic or dilution effects being observed for P and S, depending largely on SOC levels. Additionally, interactions between excreta types can result in dilution or antagonistic effects on Mn and Se uptake. Notably, high SOC combined with faeces reduces Mn and Se in forages, raising concerns for grazed ruminant systems under certain biotic situations, e.g., due to insufficient soil Se levels typically observed in UK pastures for livestock growth. These findings underscore the importance of considering SOC and excreta nutritional composition when designing forage management to optimize nutrient uptake. It should be noted that these findings have potential ramifications for broader studies of sustainable agriculture through system-scale analyses, as the granularity of results reported herein elucidate gaps in knowledge which could affect, both positively and negatively, the interpretation of model-based environmental impact assessments of cattle and sheep production (e.g., in the case of increased yields [beneficial] or the requirement of additional synthetic supplementation [detrimental]).